Psychological health and wellbeing of primary healthcare workers during COVID-19 pandemic in Malaysia: a longitudinal qualitative study - Khoo, Ee Ming; Adina, Abdullah; Liew, Su May; Norita, Hussein; Nik Sherina, Hanafi; Lee, Ping Yein; Khatijah Lim, Abdullah *; Lelamekala, Vengidasan; Ahmad Ihsan, Bin Abu Bakar; Pinnock, Hilary; Jackson, Tracy (BMC, 2022)
Background: Primary healthcare workers (PHCWs) are at the frontline of dealing with viral pandemics. They may experience significant psychological stresses, which have hitherto not been examined in depth. We aimed to explore the impact of the COVID-19 pandemic on the psychological health and wellbeing of frontline PHCWs in Malaysia.